NMR investigation of the behavior of chlorpyrifos and methyl parathion sorbed on clays, and quantitative carbon-13 NMR analysis of sequence distributions in poly(ethylene-co-1-hexene) - Seger, Mark R., author; Maciel, Gary E., advisor (Colorado State University. Libraries, 2008)
Chapters 1 and 2 (and Appendix). Decomposition of chlorpyrifos and methyl parathion on kaolinite and various cation-exchanged montmorillonites (at room temperature, in the dark) was monitored by 31P NMR. Decomposition products included the results of hydrolysis reactions, isomerization reactions and oxidation reactions; mineralization also appears to occur in some cases. Assignments of 31P peaks was based mostly on literature values of chemical shifts of similar structures and 31P NMR experiments on DMSO-d6 extracts of the pesticide/clay samples. When initially sorbed onto the clay, both pesticides appear by solid-state 31P NMR to exhibit significant motion on the molecular level, resulting in almost liquid-like spectra. Over a period of days or weeks, the signal due to unreacted pesticide diminishes and was replaced by new 31P NMR signals arising from various decomposition products. The rate of pesticide decomposition was found to vary greatly, depending on the cation present in montmorillonite. The fastest initial decomposition (disappearance of unreacted pesticide) occurred with the Cu2+-exchanged montmorillonites. Higher hydration levels of Al-exchanged montmorillonite were found to reduce the decomposition rate of methyl parathion; similarly, chlorpyrifos decomposed more quickly when sorbed on Zn-montmorillonite with lower hydration levels. Chapter 3. Different 13C NMR methods of determining triad distributions in two poly(ethylene-co-1-hexene) copolymers are examined using high signal-to-noise 126 MHz 13C spectra of the copolymers dissolved in deuterated 1,2,4-trichlorobenzene at 398K. This examination includes three integration techniques, the experimental impact of decoupler sidebands and significantly non-equal 13C nOe values. A least-squares regression analysis technique for solving for triad mole fractions is tested and appears to be more reliable than two published algebraic expressions. The resultant triad mole fractions are compared to sequence distribution parameters expected by Bernoullian and first-order Markovian statistical models. On the basis of 13C NMR-determined average reactivity ratios, the copolymer designated sample H (5.3 mol % 1-hexene) appears to be a Bernoullian copolymer resulting from a single-site catalytic system. The copolymer designated sample L (3.6 mol % 1-hexene overall) is better described as a mixture of polyethylene and a Bernoullian copolymer with 6.4 mol % 1-hexene content.
Keywords: carbon-13; chlorpyrifos; clays; methyl parathion; NMR; poly(ethylene-co-1-hexene); sequence distributions; analytical chemistry; physical chemistry